Survival prognostic factors of gastro-enteric-pancreatic neuroendocrine tumors after primary tumor resection in a single tertiary center: Comparison of gastro-enteric and pancreatic locations. Issue 6 (June 2015) - Russolillo, N.; Vigano', L.; Razzore, P.; Langella, S.; Motta, M.; Bertuzzo, F.; Papotti, M.; Ferrero, A.
Abstract Aim This study aimed to evaluated prognostic factors of patients with GEP-NETs after primary tumor resection comparing pancreatic and gastro-enteric locations. Methods Patients undergone surgery for primary GEP-NETs between 01/2000 and 03/2012 were considered. All specimens were reclassified according to the WHO 2010 scheme. Results A total of 83 patients were considered: 37 pancreatic NETs (pNET) and 46 gastroenteric NETs (GE-NET). The two groups were similar in terms of age, sex and tumors size. A higher rate of patients with pNETs had Ki67 score ≥3 (64.8% vs. 39%, p = 0.027) while the rates of Mitotic Index ≥2x10HPF (62% pNET vs. 50% GE-NET, p = 0.374) and diagnosis of neuroendocrine carcinoma NEC (16.2% pNET vs. 17.3% GE-NET, p = 0.100) were similar. The rates of distant metastases (GE-NETs 30.4% vs. p-NETs 29.7%, p = 0.944) and liver metastases (19.5% GE-NET vs. 27% pNET, p = 0.421) were comparable. Radical resection was achieved in a similar proportion in both groups [33 patients (89.1%) pNET vs. 36 (78.2%) GE-NET, p = 0.393]. After a median follow-up of 47.1 months overall 3, 5 and 10-years survival rates of whole patients were 88.1%, 81.2% and 76.7%. There was not difference on 5-years overall survival between pNET (81.4%) and GE-NET (81%, p = 0.901). At multivariate analysis age ≥70 [OR 4.177 (CI 95% 1.26–13.8), p = 0.019] and NEC [OR 5.932 (CI 95% 1.81–19.40), p < 0.001] were negative prognostic factors of survival. Conclusion Overall survival of GEP-NET after resection of primary tumors seems to be correlated to patient's age and WHO 2010 staging system but not to primary tumor site.